Unerwünschte Monumente : Moderne Kunst im Stadtraum - Grasskamp, Walter; Ammann, Jean-Christophe; Buchloh, Benjamin H.D.; Bussmann, Klaus; Calvocoressi, Richard; Fisch, Rudolf; Gamboni, Dario; Sabisch, Christian (München : Verlag Silke Schreiber München, 1993)
Aeschbacher, Hans ; Armajani, Siah ; Balkenhol, Stephan ; Baumgarten, Lothar ; Bechtold, Hubert ; Breker, Arno ; Burton, Scott ; Butler, Reg ; Chadwick, Lynn ; Egloff, Anton ; Epstein, Jacob ; Fischli & Weiss ; Fritsch, Katharina ; Fritzli ; Genzken, Isa ; Geoffrey, Clarke ; Hepworth, Barbara ; LeWitt, Sol ; Metzel, Olaf ; Moore, Henry ; Oldenburg, Claes ; Schütte, Thomas ; Serra, Richard ; Vostell, Wolf ; Weber, Bruno
boek